CREATE INNOVATIVE QUALITIES OF FUTURE SPECIALISTS OF SOCIAL SPHERE - Радченко, М. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The problem of forming innovative qualities of future social workers. Based on the analysis of scientific literature highlights the major features innovative, adapted personality. Highlights different strategies of forming such a person. The results of the level of creativity in students – future managers of social sphere. Proposed theme of role-playing games. The importance of the use in the training of educational strategies aimed at creating innovative traits